An Illini place : building the University of Illinois campus - Tate, Lex; Franch, John, 1967- (University of Illinois Press, 2017)
"This project is an interpretive and thematic look at the Urbana-Champaign campus from 1867 through 2015 via its planning, architecture and landscaping. It includes chapters that apply nine themes across time; a chapter on campus icons, most still standing; and a chapter of buildings, arenas and other spaces made possible by private gift money. Primary sources include correspondence, official reports, dedication programs and the like housed in the University Archives; transcripts of oral histories done outside the University; interviews by the authors; and other common sources. It is rich in archival research but is written for a lay audience that might wonder: Why does the University of Illinois campus at Urbana-Champaign look as it does today? A web companion to the book, hosted by the University of Illinois Press, includes short stories about ten planners, architects and presidents who were key to the campus's physical development, and inventories of campus plans and buildings, current and long-gone"--